2019
DOI: 10.4103/jcd.jcd_43_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial efficacy of 20% Punica granatum, 0.2% chlorhexidine gluconate, and 2.5% sodium hypochlorite used alone or in combinations against Enterococcus faecalis: An in-vitro study

Abstract: Objectives:The study was aimed at evaluating the antimicrobial efficacy of 20% Punica granatum, 0.2% chlorhexidine (CHX) gluconate, and 2.5% sodium hypochlorite used alone or in combinations against Enterococcus faecalis.Materials and Methods:Aqueous extract of pomegranate peel was prepared in the Pharmacology Departmental Laboratory. A total of 240 wells were prepared (40 for each group) with 5 wells per with a diameter of 6 mm and depth of 4 mm at equidistant from each other. Using a pipette, each well was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
1
23
0
2
Order By: Relevance
“…Herbal groups such as pomegranate extract, Tulsi extract and Myrrh (Commiphora molmol) are easily available and commonly used for their medicinal value. [ 2 3 9 10 ] Hence, these herbal agents were tried to evaluate their effect on root canal species in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbal groups such as pomegranate extract, Tulsi extract and Myrrh (Commiphora molmol) are easily available and commonly used for their medicinal value. [ 2 3 9 10 ] Hence, these herbal agents were tried to evaluate their effect on root canal species in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that mixture of sodium hypochlorite with P. granatum and CHX demonstrated the greatest mean zones of inhibition. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Data are conflicting however. For example, using the secondary outcome measures of microbial culture in vitro , 2% CHX had superior bactericidal properties to sodium hypochlorite (2.5%) on Enterococcus faecalis [ 88 ]. Conversely, after longer periods of irrigation for 20‐minutes, 2.5% sodium hypochlorite was more effective at preventing bacterial growth than 2% CHX [ 89 ].…”
Section: Uses For Oral Diseasementioning
confidence: 99%
“…It is also able to survive in extreme conditions and are resistant to phagocytosis and antimicrobial agents. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%